Analýza vývoja dysplázie bedrových kĺbov u psov - Ledecký, V; Sevcík, A; Capík, I; Trbolová, A (Veterinarni medicina, 1997)
Hip joint dysplasia in dogs occurs mainly in large and heavy breeds. It brings about changes on the acetabulum (socket) and the head of thigh bone, thus causing pain, tiredness, refusal to jump and refusal of increased activity. Even though presently the genetic basis of development of this disease, numerous literary sources indicate existence of pre-disposing factors that facilitate development in later stages of life. Diet and unbalanced development of skeleton and support tissues-ligaments, joint capsule and musculature also have the effect on development of dysplasia. We have analyzed acquired results of X-ray examination of dogs-German shepherds. The size of the group was 4 206 and the examination was aimed at incidence of hip-joint dysplasia during the period of 1977-1995 in the Slovak Republic. We have found out that in 1977 there were 70.7% positive cases out of the total number of examined individuals. Gradual exclusion of dogs with heavier grades of dysplasia (D, E) decreased occurrence of dysplasia to current rate of 40.8%. We considered it to be a high incidence rate. Internal structure of the positive group has changed. The number of dogs with the lightest grade of dysplasia (B) has increased, while the number of heavier grade dysplasia (C, D, E) decreased. In other breeds of dogs, of which more than 20 have been examined at the clinic, the following results have been acquired: Slovak chuvash-32%, Bavarian and Hannover bloodhound-30.6%, Rotweiler-28.6%, Newfoundland dog-26.3%, Bern sheep-dog-13.6%. At the same time we analyze the incidence of dysplasia in dogs whose parents were negative. Group of descendants of 11 negative males and 28 females consisted of 73 dogs. Through x-ray examination, 42.5% of dogs were found to have dysplasia B, C and D at the age of 1 year.
Keywords: kyčelní kloub; Dogs; Slovakia; Slovenská republika; radiografie; zvířata; Hip Joint; dysplazie kyčelního kloubu u psů; psi; Hip Dysplasia, Canine; Radiography; Animals